Ascophyllum nodosum Extract Biostimulant Processing and Its Impact on Enhancing Heat Stress Tolerance During Tomato Fruit Set - Carmody, Nicholas; Goñi, Oscar; Łangowski, Łukasz; O’Connell, Shane (Frontiers in Plant Science, 2020)
The application of biostimulants derived from extracts of the brown seaweed Ascophyllum nodosum has long been accepted by growers to have productivity benefits in stressed crops. The impact of the processing method of the A. nodosum biomass is also known to affect compositional and physicochemical properties. However, the identification of the mechanisms by which processing parameters of Ascophyllum nodosum extracts (ANEs) affect biostimulant performance in abiotically stressed crops is still poorly understood. In this study, we performed a comparative analysis of two carbohydrate-rich formulations derived from A. nodosum: C129, an ANE obtained at low temperatures through a gentle extraction and the novel proprietary PSI-494 extracted under high temperatures and alkaline conditions. We tested the efficiency of both ANEs in unstressed conditions as well as in mitigating long-term moderate heat stress in tomato (Lycopersicon esculentum, cv. Micro Tom) during the reproductive stage. Both ANEs showed significant effects on flower development, pollen viability, and fruit production in both conditions. However, PSI-494 significantly surpassed the heat stress tolerance effect of C129, increasing fruit number by 86% compared to untreated plants growing under heat stress conditions. The variation in efficacy was associated with different molecular mass distribution profiles of the ANEs. Specific biochemical and transcriptional changes were observed with enhanced thermotolerance. PSI-494 was characterized as an ANE formulation with lower molecular weight constituents, which was associated with an accumulation of soluble sugars, and gene transcription of protective heat shock proteins (HSPs) in heat stressed tomato flowers before fertilization. These findings suggest that specialized ANE biostimulants targeting the negative effects of periods of heat stress during the important reproductive stage can lead to significant productivity gains.